Memory and Justice Abused: The 1949 trial of René Bousquet - Richard J. Golsan (Studies in 20th & 21st Century Literature, 1999)
On the morning of June 8, 1993, one Christian Didier arrived at 34 rue Raphael, a posh apartment building in Paris's sixteenth arrondissement and the residence of René Bousquet, former head of Vichy police…
Keywords: Christian Didier; Paris& #x27; s sixteenth arrondissement; Paris; René Bousquet; Vichy; Vichy Police